(untitled) (Docentes 2.0 Journal, 2025)
Curricular transversality as a pedagogical strategy proposes innovating learning processes directly in the classroom, responding to the challenges of a constantly evolving society in a transformative and integrative manner. The present study aimed to analyze the diverse perspectives of the transversal curriculum in educational processes, compiling significant contributions that contribute to a comprehensive understanding of the topic. The research employed a systematic method, an interpretive paradigm, and a qualitative approach, with a thematic narrative design that combined analytical documentary and cross-sectional elements. The PRISMA method was used to select and analyze 30 relevant articles published since 2018. This research was conducted through the search engines Google Scholar, Dialnet, Scielo, and Research Gate. The relevance of transversality for the comprehensive education of students is evident, as is the flexibility of this pedagogical proposal, and the commitment of school agents, especially teachers, to achieve successful planning and execution of this strategy. Furthermore, it documents the essential nature of the mainstreaming process: rigorous planning, the selection of appropriate content, and integrative thematic axes linked to the environment and reality of students and their communities, which spark the interest of learners. This review serves the dual purpose of validating its usefulness. Thus, this systematic review contributes to pedagogy and education, especially in primary education, by compiling and demonstrating the multiple benefits of mainstreaming and the key aspects for its successful implementation.